2014
DOI: 10.1088/0004-637x/786/2/156
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Wavelength View of the Central Kiloparsec Region in the Luminous Infrared Galaxy NGC 1614

Abstract: The Luminous Infrared Galaxy NGC 1614 hosts a prominent circumnuclear ring of star formation. However, the nature of the dominant emitting mechanism in its central ∼ 100 pc is still under debate. We present sub-arcsecond angular resolution radio, mid-infrared, Paα, optical, and X-ray observations of NGC 1614, aimed at studying in detail both the circumnuclear ring and the nuclear region. The 8.4 GHz continuum emission traced by the Very Large Array (VLA) and the Gemini/T-ReCS 8.7 micron emission, as well as th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(61 citation statements)
references
References 69 publications
4
57
0
Order By: Relevance
“…Numerical simulations suggest that the burst was triggered after a minor merger (Väisäinen et al 2012). In their multiwavelength study, Herrero-Illana et al (2014) concluded that there is no evidence of an AGN in the nucleus of NGC 1614 down to an AGN-to-bolometric luminosity ratio of <10%. In agreement with this picture, not detecting the nuclear source in the 435 µm continuum image of the galaxy obtained with ALMA led Xu et al (2015) to rule out a Compton-thick AGN in NGC 1614.…”
Section: Ngc 1614mentioning
confidence: 99%
“…Numerical simulations suggest that the burst was triggered after a minor merger (Väisäinen et al 2012). In their multiwavelength study, Herrero-Illana et al (2014) concluded that there is no evidence of an AGN in the nucleus of NGC 1614 down to an AGN-to-bolometric luminosity ratio of <10%. In agreement with this picture, not detecting the nuclear source in the 435 µm continuum image of the galaxy obtained with ALMA led Xu et al (2015) to rule out a Compton-thick AGN in NGC 1614.…”
Section: Ngc 1614mentioning
confidence: 99%
“…(iii) As found in Herrero-Illana et al (2014) based on the thermal vs non-thermal emission relation, regions A and B (see Fig. 1, top) are the most prone to harbor supernovae.…”
Section: The Nature Of the Off-nuclear Compact Sourcementioning
confidence: 60%
“…From the dozens of compact sources detected in Arp 299 (Pérez-Torres et al 2009;Bondi et al 2012), only eight are above our 5σ detection threshold (7.4 × 10 26 erg s −1 Hz −1 ) and have a SN origin. Furthermore, the supernova rate obtained through consistent SED multiwavelength modeling is higher for Arp 299 ( 0.8 SN yr −1 ; Mattila et al 2012) than for NGC 1614 ( 0.4 SN yr −1 ; Herrero-Illana et al 2014). Therefore, we would expect four SN detections in our observations.…”
Section: The Nature Of the Off-nuclear Compact Sourcementioning
confidence: 71%
See 2 more Smart Citations